Comparison of in vitro and in vivo fertilizing potential of bovine semen frozen in egg yolk or new lecithin based extenders - Crespilho, A. M.; Sa Filho, M. F.; Dell'aqua Junior, José Antônio [UNESP]; Nichi, M.; Monteiro, G. A. [UNESP]; Avanzi, B. R. [UNESP]; Martins, A. [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier B.V., 2012)
One of the main factors known to influence quality and fertility of bovine cryopreserved semen is the extender used. In this matter, a great worldwide interest has been directed to the development of chemically defined media, free of animal origin products. The objective of the present study was to compare the efficacy of three bovine semen extenders: Iris-fructose (IRIS, control with 20% egg yolk), Botu-Bov (R) (BB; 20% egg yolk), and Botu-Bov (R)-soy lecithin (BB-L; 1% soy lecithin). Towards this aim, post-thaw computer assisted sperm analysis (CASA), sperm membrane and acrosome integrity were evaluated (Experiment 1). Additionally, cryopreserved samples were used in a fixed time artificial insemination program aiming to evaluate in vivo fertility (pregnancy per insemination-P/AI; Experiment 2). Despite the higher straightness and linearity found for samples cryopreserved in BB and BB-L when compared to those cryopreserved in IRIS, egg yolk based extenders provided higher total and progressive motilities, percentage of rapid sperms and intact membrane cells (P < 0.05). Furthermore, P/IA was higher in samples cryopreserved in egg yolk based extenders when compared to soy lecithin [TRIS=59.26(a) (64/108), BB=62.37(a) (58/93), and BB-L=36.45(b) (35/96)]. Although soy lecithin represents an alternative for the development of chemically defined extenders with decreased risk of biological contamination, egg yolk based extenders are more efficient on the preservation of bovine post-thaw sperm viability and fertility. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Bull semen; Semen extender; Egg yolk; Soy lecithin; Cryopreservation; Artificial insemination